The effect of pension wealth on private savings. Results from an extended life cycle model - Zhiyang Jia; Weizhen Zhu (Statistics Norway, Research Department, 2012)
An extended life cycle model is used to investigate how variation in the level of expected pensions influences non-pension wealth accumulation. We try to explain why the offset effects between pension wealth and private savings are not one to one by accounting for different risks and market imperfections, which includes uninsured risk on earnings, mortality risk, borrowing constraints and bequest motive. The model is calibrated on Norwegian household data from 1992 to 2005. Based on the calibrated model, simulations are performed to explore consequences of introducing these factors. The result shows that by simply accounting these risks and constraints, we can explain most of the departure between empirical findings and theoretical prediction.
Keywords: D91; 330; Life cycle model; Offset effect; pension wealth; private savings